Synthesis of graphene oxide–metal nanoparticle nanocomposites for catalytic reduction of nitrocompounds in aqueous medium. Issue 1 (1st January 2021) - Naeem, Hina; Ajmal, Muhammad; Khatoon, Fatima; Siddiq, Muhammad; Khan, Gul Shahzada
Abstract : Graphene oxide templated cobalt (GO–Co) and graphene oxide templated silver (GO–Ag) nanocomposites were synthesized and used as catalysts in the reduction of 4-Nitrophenol (4-NP), 2-Nitrophenol (2-NP) and 2-Nitroaniline (2-NA). Almost evenly distributed nanoparticles of Ag and Co were obtained on GO sheets and the diameters of most of the particles were in the range of 5–15 nm. The maximum apparent reduction rate ( k app ) for 4-NP was found to be 0.58 min −1 and 0.67min −1 with corresponding activation energies of 28.79 and 16.54 kJ mol −1 in the presence of GO–Ag and GO–Co catalysts, respectively. The k app for GO–Co cataly-zed reduction of 2-NP and 2-NA were found as 0.10 and 0.06 min −1, respectively. Catalytic activity of GO–Ag was decreased by 25% in the fifth cycle while that of GO–Co was decreased to 47% in the fourth cycle for the reduction of 4-NP. Overall, GO–Ag showed superior catalytic behaviour as compared to GO–Co.